A catalyst for electrocatalytic nitrate reduction to produce ammonia, and its preparation method and application
By uniformly electrodepositing the electrocatalyst of copper-cobalt nickel sheets on nickel foam, the problem of low efficiency and yield of nitrate reduction is solved, efficient and environmentally friendly ammonia production and nitrate removal are achieved, and a variety of wastewater environments are adapted to Meet industrial needs.
Patent Information
- Application Number
- CN202210683098.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-06-16
AI Technical Summary
In the prior art, the Faraday efficiency and ammonia yield of nitrate reduction to ammonia are difficult to meet industrial needs and are sensitive to the environment, especially when treated in high concentration nitrate solutions, which are difficult to meet the needs of practical applications.
Copper-cobalt nickel sheets uniformly electrodeposited on nickel foam are used as electrocatalysts, with the molar percentage of copper and cobalt elements ranging from 20-70%: 30-80%. Electrocatalytic nitrate reduction under normal temperature and pressure conditions. The platinum sheet is used as a counter electrode to prepare the catalyst by constant current electrode deposition.
Achieve high ammonia-yield Faraday efficiency and ammonia yield. The unit mass rate of ammonia production is better than that of the traditional Haber-Bosch process. The ammonia-yield Faraday efficiency is above 90%, adapts to a variety of wastewater environments, and has high nitric acid in high concentration nitrate solutions. The salt removal rate and nitrate residue are lower than the drinking water limit.
Smart Images

Figure CN115233253B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nitrate reduction to produce ammonia, and specifically relates to an electrocatalytic nitrate reduction to produce ammonia catalyst, a preparation method and application thereof. Background Art
[0002] Nitrate anion (NO3 - ) is widely present in industrial and agricultural wastewater, posing a serious threat to human health and ecological balance, especially its incomplete conversion will generate nitrite (NO2 - ), which is considered a carcinogen by inducing liver damage and methemoglobinemia.
[0003] Traditionally, NO3 - The conversion and removal of NO3 is mainly carried out in two directions: (1) reduction to nitrogen (N2) through the denitrification process of the sewage treatment plant; (2) reduction to ammonia (NH3) through nitrate / nitrite reductase secreted by microorganisms (such as Shewanella oneidensis cytochrome c nitrite reductase). - Reduction to NH3 is of greater interest from an industrial perspective, as NH3 is a very important industrial chemical that is widely used in the synthesis of drugs, fertilizers, dyes, plastics, etc., and is also used as a hydrogen storage / release carrier for carbon-free hydrogen carriers. However, to date, the industrial synthesis of NH3 has relied heavily on the unsustainable and eco-unfriendly Haber-Bosch route, which requires harsh conditions of high temperature (400-600°C), high pressure (200-350atm), and the source of hydrogen as a raw material relies heavily on fossil energy. In fact, the total amount of carbon dioxide produced during the Haber-Bosch process accounts for about 1.2% of the global annual carbon dioxide emissions.
[0004] By utilizing denitrifying microorganisms in the natural environment, NO3 - Biocatalytic reduction to NH3 (called bio-NRA) is an emerging, sustainable and environmentally friendly technology that can convert difficult-to-treat nitrate pollutants into high-value products. These high-value products can be obtained by physical and chemical methods such as ion exchange adsorption and struvite precipitation to obtain NH3 precipitates for further industrial applications. However, the biocatalytic system of bio-NRA is time-consuming and has a low NH3 yield, which is far from the Haber-Bosch route and is difficult to meet actual industrial needs. In addition, bio-NRA is very sensitive to the environment of the wastewater to be treated. For example, NO3 in mining wastewater - High concentration (more than 2500 mg L -1) and low organic matter content will limit the reproduction and growth of microorganisms. Therefore, in order to fill the gap between the limited biocatalysis in nature and the high demand for environmental remediation, scientists began to introduce the functions of microbial enzymes into artificial synthetic chemical materials that are easy to prepare in batches, and use renewable electricity for reduction drive to achieve low-carbon, environmentally friendly and efficient nitrate reduction to produce ammonia.
[0005] In bio-NRA, nitrate reductase accepts electrons from quinone to convert NO3 - Reduction to NO2 - , the NO2 produced - It is further converted into NH3 by nitrite reductase (NIR). Among various NIR, copper-type NIR (Cu-NIR) widely present in rhizobia has been widely studied by scientists. Cu-NIR contains a trimer protein composed of 3 identical subunits. There are two types of copper atoms in each enzyme monomer, which act as electron donor center (T1Cu) and catalytic center (T2Cu). Its mechanism of action is *NO2 - (where * represents the adsorbed substance) binds to T2Cu in a bidentate form through two oxygen atoms, electrons are transferred from T1Cu to T2Cu, and the oxidation state of T2Cu decreases from (II) to (I), promoting *NO2 - It binds to T2Cu in the form of a bridging nitro group. At the same time, the aspartic acid next to T2Cu is NO2 - One of the oxygen atoms in the N-O bond donates a proton, which stretches the N-O bond and causes the N-O bond to break.
[0006] Although Cu-NIR has a unique composition structure and excellent catalytic activity, its Faradaic efficiency for ammonia production is around 70%, and the ammonia productivity is less than 1 mmol cm -2 h -1 Although many researchers have modified Cu-NIR in the prior art and increased the Faradaic efficiency of nitrate reduction to produce ammonia to more than 90%, the ammonia productivity still cannot meet the needs of practical applications. Summary of the invention
[0007] The present invention aims to overcome the defects of the prior art and provide a catalyst for electrocatalytic nitrate reduction to produce ammonia.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned electrocatalytic nitrate reduction catalyst for producing ammonia.
[0009] Another object of the present invention is to provide an application of the above-mentioned electrocatalytic nitrate reduction catalyst for producing ammonia.
[0010] The technical solution of the present invention is as follows:
[0011] The invention discloses an electrocatalytic nitrate reduction ammonia production catalyst, wherein the effective components thereof include a copper-cobalt-nickel sheet composed of nickel foam and copper and cobalt elements uniformly electrodeposited on the nickel foam, wherein the molar percentage of the copper element and the cobalt element in the copper-cobalt-nickel sheet is 20-70%:30-80%.
[0012] In a preferred embodiment of the present invention, the molar percentage of copper element to cobalt element in the copper-cobalt-nickel sheet is 45-55%:45-55%.
[0013] Further preferably, the molar percentage of copper element and cobalt element in the copper-cobalt-nickel sheet is 50%:50%.
[0014] In a preferred embodiment of the present invention, the active ingredient is the copper-cobalt-nickel sheet, and the thickness of the copper-cobalt-nickel sheet is 8-11 nm.
[0015] The preparation method of the electrocatalytic nitrate reduction catalyst for ammonia production comprises: using a nickel foam with surface contaminants removed as a working electrode and a platinum sheet as a counter electrode in an electroplating solution at 0.04-0.06Acm -1 The copper-cobalt-nickel sheet is obtained by performing constant current electrodeposition for 250-350 seconds at a current density of , wherein the electroplating solution consists of soluble copper salt, soluble cobalt salt, trisodium citrate and ultrapure water, and the molar ratio of the total amount of soluble copper salt and soluble cobalt salt to trisodium citrate is 10:3.
[0016] In a preferred embodiment of the present invention, the total concentration of the soluble copper salt and the soluble cobalt salt in the electroplating solution is 0.05 mol / L, and the concentration of the trisodium citrate in the electroplating solution is 0.015 mol / L.
[0017] In a preferred embodiment of the present invention, the soluble copper salt is at least one of copper sulfate, copper chloride, copper acetate and copper nitrate, and the soluble cobalt salt is at least one of cobalt sulfate, cobalt chloride, cobalt acetate and cobalt nitrate.
[0018] A copper-cobalt-nickel sheet is used as a catalyst for electrocatalytic nitrate reduction to produce ammonia. The copper-cobalt-nickel sheet is composed of nickel foam and copper and cobalt elements uniformly electrodeposited on the nickel foam, and the molar percentage of copper and cobalt in the copper-cobalt-nickel sheet is 20-70%:30-80%.
[0019] In a preferred embodiment of the present invention, the molar percentage of copper element to cobalt element in the copper-cobalt-nickel sheet is 45-55%:45-55%.
[0020] Further preferably, the molar percentage of copper element and cobalt element in the copper-cobalt-nickel sheet is 50%:50%.
[0021] A method for producing ammonia by reducing nitrate, using the electrocatalytic nitrate reduction catalyst for producing ammonia as a self-supporting integrated electrode to electrocatalytically reduce nitrate to produce ammonia in an electrochemical system.
[0022] The beneficial effects of the present invention are:
[0023] 1. When the present invention uses clean electric energy to perform electrocatalytic nitrate reduction to produce ammonia under normal temperature and pressure conditions, it has excellent Faraday efficiency and ammonia yield for ammonia production, which exceeds the catalytic performance of most of the currently reported electrocatalysts for nitrate reduction to produce ammonia, and the unit mass rate of ammonia production is significantly better than that of the traditional Haber-Bosch process.
[0024] 2. The present invention can maintain ammonia production Faraday efficiency of more than 90% in a wide potential range of -0.1-0.4V vs. RHE, and can achieve ammonia production efficiency of 1-100mmol L -1 Wide NO3 - Within the concentration range, the Faraday efficiency of ammonia production at -0.1Vvs.RHE is maintained above 95%, which can adapt to a variety of wastewater environmental systems and maintain good NO3 - Recycling capabilities.
[0025] 3. The stability of the Faraday efficiency of ammonia production of the present invention is good.
[0026] 4. The present invention has a very high nitrate removal rate when batch processing high-concentration nitrate solutions, and the residual nitrate in the solution after the processing is completed is lower than the drinking water limit specified by the World Health Organization. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The experimental results of Example 1 of the present invention are shown in Figure 1, wherein (a) is a schematic diagram of in-situ electrodeposition of a copper-cobalt alloy catalyst on nickel foam; (b) is an X-ray diffraction pattern (XRD) of catalysts with different copper-cobalt ratios; and (c) is a high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM) of different catalysts: (f) Cu, (d) and (g) Cu 50 Co 50 , (e)(h):Co.
[0028] Figure 2 The experimental results of Example 1 of the present invention are shown in FIG. 50 Co s0 Linear voltammetric curves (v = 1 mV s -1 )(a) and the corresponding Tafel slope in the potential range of -0.2-0.1 V vs. RHE (b); (c) Cu 50 Co 50Linear voltammetric curves of the catalyst at different rotation speeds and the number of electron transfers at different potentials calculated by the KL equation; Faraday efficiency (d) and product yield and current density (e) of the products of nitrate reduction catalyzed by catalysts with different copper-cobalt ratios deposited on nickel foam at a potential of 0 V vs. RHE; Cu 50 Co 50 Faradaic efficiency (f) and yield (g) of the products of Cu / Ni foam, Cu / Ni foam and Co / Ni foam catalysts at different electrode potentials; (h) Cu 50 Co 50 / Ni foam catalyst in a unidirectional flow cell at -0.1V vs.RHE constant potential electrolysis for 24 h and the current density and Faraday efficiency of ammonia production; (i) 50 Co 50 / Ni foam was electrolyzed at a constant potential of -0.1V vs.RHE. - , NO2 - and the changes of NH3 concentration and FE with time. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0030] Example 1
[0031] (1) Prepare the plating solution according to Table 1:
[0032] Table 1 Plating solution components
[0033]
[0034] (2) (1×1cm 2 ) Rectangular nickel foam (thickness: 2 mm, 75 ppi) was ultrasonically cleaned in acetone, ethanol, and ultrapure water solution for 10 min to remove surface contaminants. The ultrasonic power was 100 W and the ultrasonic frequency was 40 kHz.
[0035] (3) The nickel foam washed in step (2) was used as the working electrode (1×1 cm 2 ) platinum sheet as the counter electrode, respectively, in the plating solution of the corresponding ratio as shown in Table 1, using a constant current meter, at 0.05A cm -1 At a current density of , constant current electrodeposition was performed for 300s to obtain pure Cu catalyst and Cu 70 Co 30 Catalyst, Cu 50 Co 5o Catalyst, Cu 20 Co 80catalyst and pure Co catalyst.
[0036] (4) The pure Cu catalyst and Cu 70 Co 30 Catalyst, Cu 50 Co 50 Catalyst, Cu 20 Co 80 The catalyst and pure Co catalyst were placed in ultrapure water and stirred for washing 5 times, dried with argon gas and set aside.
[0037] In this example, a scanning electron microscope (SEM, ZEISS Sigma) with an X-ray spectrometer was used to measure the pure Cu catalyst, Cu 70 Co 30 Catalyst, Cu 50 Co 50 Catalyst, Cu 20 Co 80 The morphology and elemental composition of the catalyst and the pure Co catalyst were characterized. The pure Cu catalyst, Cu 70 Co 30 Catalyst, Cu 50 Co 50 Catalyst, Cu 20 Co 80 The lattice arrangement of the catalyst and the pure Co catalyst was observed. The pure Cu catalyst, Cu 70 Co 30 Catalyst, Cu 50 Co 50 Catalyst, Cu 20 Co 80 The chemical composition of the pure Cu catalyst, Cu 70 Co 30 Catalyst, Cu 50 Co 50 Catalyst, Cu 20 Co 80 The crystal structure of the pure Cu catalyst, Cu 70 Co 30 Catalyst, Cu 50Co 50 Catalyst, Cu 20 Co 80 The surface chemical states of the catalysts and pure Co catalysts were analyzed. All XPS spectra were calibrated with the C1s line at 284.8 eV.
[0038] X-ray diffraction (XRD) results show that ( Figure 1 (b)), the compositions of pure Cu catalyst and pure Co catalyst are zero-valent metal copper and metal cobalt, respectively; Cu 70 Co 30 Catalyst, Cu 50 Co 50 Catalyst and Cu 20 Co 80 The catalysts all showed the characteristics of alloys, with no corresponding metal diffraction peak signals, and with the addition of cobalt, the copper diffraction peak gradually shifted to a higher angle. This means that the cobalt element with a smaller atomic radius was successfully incorporated into the copper metal, resulting in a contraction of the lattice spacing. Using a high-resolution transmission electron microscope, it was observed that Cu 50 Co 50 The lattice spacing of the Cu(111) crystal plane of the catalyst is 0.208nm ( Figure 1 This is in contrast to the Cu(111) lattice spacing of 0.210 nm observed in pure Cu catalyst ( Figure 1 (c)) shows a significant contraction compared to the Co(111) lattice spacing of 0.206 nm observed in the pure Co catalyst ( Figure 1 (e)) shows lattice expansion, which is consistent with the XRD results.
[0039] This example also uses an electron microscope (SEM) to observe the morphology of the catalyst. When the catalyst is mainly composed of copper, the catalyst presents a dendrite structure composed of particles of tens of nanometers. When the cobalt content exceeds 50% (Cu 50 Co 50 , Cu 20 Co 80 and Co), the catalyst exhibits a dendrite-like structure of three-dimensional nanosheet stacking ( Figure 1 (g) and Figure 1 (h)). Atomic force microscopy showed that Cu 50 Co 50 The thickness of the catalyst nanosheet is about 10 nm. In addition, through X-ray photoelectron spectroscopy (XPS), this example observed that the Cu 2p spectra of different catalysts all have Cu 2+Characteristic peaks indicate that the catalyst surface is partially oxidized by oxygen in the air. The Co 2p spectrum also shows characteristic peaks of Co oxides. In addition, the Co 2p binding energy of the alloy catalyst is significantly increased compared with that of the pure Co catalyst. This may be because the copper-cobalt alloying affects the distribution of electrons, causing the Co 3d energy band to move in the opposite direction of the Fermi level. This is likely to change the adsorption energy of the catalyst for the intermediate products of the nitrate reduction reaction (eg: *H and *NO3).
[0040] Example 2
[0041] (1) Reagent preparation:
[0042] A. Preparation of nitrate reduction electrolyte: Weigh 28.055 g of KOH solid into a beaker and add water to dissolve it. After the solution temperature drops to room temperature, transfer it to a 500 mL flask and make up to volume to obtain 1 mol L -1 KOH solution. Weigh 5.055g KNO3 and 28.055g KOH in a beaker and add water to dissolve. After the solution temperature drops to room temperature, transfer it to a 500mL flask and make up to volume to obtain 100mmol L -1 KNO3 and 1 mol L -1 Mixed solution of KOH. Take 1mL, 5mL, 10mL and 50mL of 0.1mol L -1 KNO3 and 1 mol L -1 The mixed solution of KOH was placed in different 100 mL volumetric flasks and 1 mol L -1 KOH solution was made up to volume to obtain 1 mmol L -1 , 5mmol L -1 、10mmol L -1 and 50mmol L -1 KNO3 and 1 mol L -1 KOH mixed solution
[0043] B. Preparation of electrodeposition solutions of different copper salts and cobalt salts:
[0044] Chloride salt: weigh 0.1938g of copper chloride hexahydrate, 0.3285g of cobalt chloride dihydrate and 0.2207g of trisodium citrate dihydrate in 50mL of ultrapure water and dissolve for later use;
[0045] Acetate: weigh 0.2269 g of copper acetate tetrahydrate, 0.3395 g of cobalt acetate monohydrate and 0.2207 g of trisodium citrate dihydrate in 50 mL of ultrapure water and dissolve them for later use;
[0046] Nitrates: Weigh 0.2745 g copper nitrate trihydrate, 0.3969 g cobalt nitrate hexahydrate and 0.2207 g trisodium citrate dihydrate into 50 mL ultrapure water and dissolve them for later use.
[0047] (2) Specific test conditions:
[0048] A. The electrochemical tests in this example were performed on a CHI 760e electrochemical workstation using a three-electrode system. All catalysts were tested at -0.6 V vs RHE at 0.1 mol L -1 The electrochemical reduction was carried out in a deoxygenated potassium sulfate solution for 600 s. A nickel foam electrode with a catalyst was used as the working electrode, a platinum sheet was used as the counter electrode, and a mercury / mercury oxide electrode (filled with 1 mol L -1 KOH solution) as the reference electrode, with a value of 1 mV s -1 The electrochemical linear voltammetric curve was obtained in a single-cell electrolytic cell (working electrode area: 0.3*0.3cm 2 ), a constant voltage in-situ electrolysis experiment of nitrate reduction was carried out in a H electrolytic cell (working electrode area: 0.5*0.5cm -2 The results were performed using different potassium nitrate concentrations (1, 5, 10, 50 and 100 mmol L -1 ) of 1 mol L -1 KOH aqueous solution was used as the electrolyte.
[0049] B. Pure Cu catalyst, Cu 50 Co 50 The catalyst and pure Co catalyst were ultrasonically dispersed in a solvent containing a binder (600 μL isopropanol: 380 μL ultrapure water: 20 μL 5% Nafion solution) to form a uniform ink (5 mg mL -1 ). Take 10 μL of ink and load it evenly on the polished glassy carbon electrode (GCE, 0.196 cm 2 ). The glassy carbon electrode, platinum electrode and mercury / mercury oxide electrode loaded with catalyst were used as working electrode, counter electrode and reference electrode respectively, and linear voltammetric curves at different rotation speeds (100, 225, 400, 625 rpm) were obtained on a rotating disk electrode test system (with a rotator). The scan rate was 10 mV s -1 . Use a solution containing 100mmol L -1 Concentration of potassium nitrate 1 mol L -1 KOH aqueous solution was used as the electrolyte. Before all electrochemical tests, argon gas was used to remove dissolved oxygen in the electrolyte.
[0050] C. The stability test of the catalyst in this example was carried out in a flow cell. The nickel foam electrode with the catalyst deposited thereon was used as the working electrode, the platinum sheet was used as the counter electrode, and the mercury / mercury oxide electrode (filled with 1 mol L-1 KOH solution) was used as the reference electrode. -1 KNO3+1mol L -1 The electrolyte was electrolyzed at a potential of -0.1 V vs. RHE for 24 h. The electrolyte flow rate in the cathode and anode compartments was 1 mL min -1 , and the two chambers are separated by a Nafion membrane.
[0051] (3) The specific test results are as follows:
[0052] A. Through 1mV s -1 The linear voltammetric curves at low scan rates preliminarily compare Cu, Co and Cu 50 Co 50 Catalyst NO3 - RR electrocatalytic activity. Figure 2 As can be seen in (a), the current density in the electrolyte containing nitrate is much greater than that in the electrolyte without nitrate. This indicates that in the solution containing nitrate, the main contribution of the current comes from the reduction of nitrate, and the catalysts all show good nitrate reduction performance. This example uses a current density of 10 mA cm -2 The overpotential required for the current density (η 10mA cm -2 , = E°-E; E° = 0.69V vs. RHE), as a comparison NO3 - The standard of RR activity. -1 KOH + 0.1 mol L - 1 In KNO3 electrolyte, Cu 50 Co 50 Catalyst The catalyst voltage is 498 mV, which is lower than that of pure Cu (503 mV) and pure Co (690 mV). At an electrode potential of 0 V vs. RHE, Cu 50 Co 50 The reduction current density of the catalyst is 145.5 mA cm -2 , which is the pure Cu catalyst (82.1 mA cm -2 ) is nearly twice that of pure Co catalyst (6mA cm -2 ) is about 20 times. In fact, in Cu and Cu 50 Co 50 Two reduction current peaks (S1 and S2) can be observed in the curve. 50 Co50 NO3 - RR showed similar behavior, indicating that Cu plays an important role in this stage of the reaction. According to previous studies, the S1 peak near 0.08 V vs. RHE is the process of reducing *NO3 species to *NO2 through 2 electron transfer (Eq. (1)), while the S2 peak is the process of reducing *NO2 species to *NH3 through 6 electron transfer (Eq. (2)). In the S2 peak region, Cu 50 Co 50 Compared with Cu, a positive potential shift of 67 mV appeared, indicating that with the increase of applied potential, there is a good synergistic effect between Co and Cu, and the potential energy barrier for the reduction of *NO2 to *NH3 decreases.
[0053] *NO3+2e - +H2O→*NO2+2OH - Eq.(1)
[0054] *NO2+6e - +5H2O→*NH3+7OH - Eq.(2)
[0055] B. In order to study the reaction routes of all catalysts, this example estimates the NO3 - The number of electrons transferred during the RR process (n). The Cu catalyst experienced a reduction process from 2e- to 6e-, verifying the reduction route described in formulas (1) and (2). 50 Co 50 In the potential region between peaks S1 and S2, only the 8e-transfer process was observed ( Figure 2 (b)), indicating that the strong alloying effect promotes both pathways. The 8-electron transfer process also occurs on the pure Co catalyst, but the electrode potential is much more negative, that is, the potential barrier is higher. Figure 2 The linear voltammetric curves of (a) were used to obtain Tafel plots for the S1 and S2 reactions. For the S1 segment (0.17-0.1 V vs. RHE), Cu 50 Co 50 The Tafel slope of the catalyst in this potential range is 205.75 mV decade. -1 , which is lower than the Tafel slope of pure Cu catalyst (232.43 mV decade -1 ) is slightly decreased, indicating that the addition of Co can promote the electron transfer at the catalyst / electrolyte interface. Pure Co catalyst has basically no electrocatalytic activity for reducing nitrate at a relatively positive electrode potential, so the Tafel slope of Co in this potential range is not considered. In the potential region of the S2 peak ( Figure 2 (b) Cu 50 Co 50 The Tafel slope of the catalyst (148.95mV decade -1 ) is also higher than that of pure Cu catalyst (229.75mV decade -1 ) has been significantly reduced. This can be explained by the fact that Cu and Co 50 Co 50 The electron redistribution on the catalyst is also confirmed by the XPS results in the characterization section. The Tafel slope value of the Co catalyst is lower, which is 94.24mV decades -1 , but the electrode potential is higher than Cu 50 Co 50 This result indicates that Co exhibits better NO3 degradation after crossing the high energy barrier compared to Cu-based catalysts. - RR reaction kinetics. Alloying Co with Cu can obtain faster electron transfer rate and improve NO3 - Dynamic performance of RR.
[0056] C. To further evaluate the NO3 - RR performance, in this example, in an H-type electrolytic cell, a catalyst is used to perform constant potential electrolytic reduction of NO3 - . Ammonia and nitrite as NO3 - The main products of RR were quantitatively detected using the nanostructured reagent method and ion chromatography. Figure 2 As shown in (d)(e), at an electrode potential of 0V vs. RHE, the pure Cu catalyst mainly produces nitrite, and the ammonia production efficiency is only 32%. With the addition of cobalt, the proportion gradually increases from 0% to 100%, the ammonia production Faraday efficiency gradually increases and then stabilizes, and the ammonia production partial current density shows a volcano-shaped relationship. When the cobalt element accounts for 50%, that is, Cu 50 Co 50 The partial current density of NO3-RR for ammonia production (347 mA cm -2 , 88% FE for NH3) is also the highest, which is the pure Cu catalyst (34mA cm -2 , 32% FE for NH3) is about 10 times that of pure Co catalyst (21mA cm -2 , 84% FE for NH3) by 17 times. The electrochemically active surface areas (ECSA) of the catalysts were measured and the ECSAs of all catalysts were comparable. 50 Co 50 The largest ECSA normalized current density was obtained on the catalyst, indicating that the catalyst has the highest ammonia production activity.
[0057] Cu 50 Co 50 The catalyst has a Faraday efficiency of 65% for ammonia production at an overpotential of only 590 mV (0.1 V vs. RHE). A portion of nitrate is still reduced to nitrite. As the electrode potential shifts negatively, the nitrite in the product decreases rapidly. At -0.2 V vs. RHE, Cu 50 Co 50 The catalyst has a Faradaic efficiency of 100±1% for ammonia production and a partial current density of 1035 mV cm -2 The corresponding ammonia production efficiency is 4.8 mmol cm -2 h -1 , which is about 2 times that of pure Co catalyst and about 8 times that of pure Cu catalyst. Figure 2 (g)). According to the charge consumed during the electrodeposition process, the deposited Cu 50 Co 50 The mass of the catalyst is used to calculate its mass activity for ammonia production (Y (mass-NH3) ) is about 960mmol g -1 h -1 , is the Haber-Bosch process (200mmol g -1 h -1 ). In the wide potential range of -0.1--0.4V vs.RHE, its Faraday efficiency of ammonia production can be maintained above 90%, but as the electrode potential continues to shift negatively, hydrogen deposition gradually increases, and the Faraday efficiency of ammonia production decreases ( Figure 2 (f)). When the copper-cobalt salts with different anions such as chloride, acetate and nitrate are used to prepare the catalyst, the Faradaic efficiency of ammonia production can reach more than 90% at -0.2V vs. RHE.
[0058] D. NO3 in wastewater in real life - The content is between 0.88-1950mmol L-1. Therefore, in this embodiment, the content is between 1-100mmol L -1 NO3 - In the concentration range, Cu 50 Co 50 The catalyst was treated with nitrate reduction. At -0.1 V vs. RHE, Cu 50 Co 50 The Faradaic efficiency of ammonia production was maintained above 95% (Figure S12). 50 Co 50 The catalyst can adapt to a variety of wastewater environmental systems and maintain good NO3 - This example also uses a unidirectional continuous flow mode to investigate the Cu on nickel foam support.50 Co 50 Catalyst NO3 - RR activity, stability and Faradaic efficiency to simulate real wastewater treatment processes at laboratory scale. 50 Co 50 When constant potential electrolysis was carried out at -0.1 V vs. RHE for 24 hours, the Faradaic efficiency of ammonia production was stabilized at about 95%, and the current density was maintained above 85%.
[0059] E. Batch treatment 100mmol L -1 (about 6,200 ppm) of high concentration nitrate solution: Figure 2 As shown in (i), at a reduction potential of -0.1 V vs. RHE, 90% of nitrate can be removed in 4 hours; after 10 hours, the nitrate removal rate reaches 99.5%, and the NH3 Faraday efficiency is 96%. The residual nitrate in the solution is only 31 ppm, which is lower than the drinking water limit of 50 ppm set by the World Health Organization. For the generated ammonia, air stripping, ion exchange, breakpoint chlorination, struvite precipitation and other methods can be considered for further extraction and purification.
[0060] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A catalyst for electrocatalytic nitrate reduction to produce ammonia, characterized in that: Its effective component is a copper-cobalt-nickel sheet with a thickness of 8-11 nm, which is composed of nickel foam and copper and cobalt elements uniformly electrodeposited on the nickel foam. The molar percentage of copper and cobalt in the copper-cobalt-nickel sheet is 50%:50%; The preparation method comprises: using the nickel foam with the surface pollutants removed as the working electrode and the platinum sheet as the counter electrode in the electroplating solution at 0.04-0.06A cm -1 The copper-cobalt-nickel sheet is obtained by constant current electrodeposition for 250-350s at a current density of , wherein the electroplating solution consists of soluble copper salt, soluble cobalt salt, trisodium citrate and ultrapure water, and the molar ratio of the total amount of soluble copper salt and soluble cobalt salt to trisodium citrate is 10:
3.
2. The electrocatalytic nitrate reduction catalyst for ammonia production according to claim 1, characterized in that: The total concentration of the soluble copper salt and the soluble cobalt salt in the electroplating solution is 0.05 mol / L, and the concentration of the trisodium citrate in the electroplating solution is 0.015 mol / L.
3. Application of copper-cobalt-nickel sheet as electrocatalytic nitrate reduction catalyst to produce ammonia, characterized by: The copper-cobalt-nickel sheet is composed of nickel foam and copper and cobalt elements uniformly electrodeposited on the nickel foam, and the molar percentage of copper and cobalt in the copper-cobalt-nickel sheet is 50%:50%, and the thickness is 8-11 nm; The preparation method comprises: using the nickel foam with the surface pollutants removed as the working electrode and the platinum sheet as the counter electrode in the electroplating solution at 0.04-0.06A cm -1 The copper-cobalt-nickel sheet is obtained by constant current electrodeposition for 250-350s at a current density of , wherein the electroplating solution consists of soluble copper salt, soluble cobalt salt, trisodium citrate and ultrapure water, and the molar ratio of the total amount of soluble copper salt and soluble cobalt salt to trisodium citrate is 10:
3.
4. The use according to claim 3, characterized in that: The total concentration of the soluble copper salt and the soluble cobalt salt in the electroplating solution is 0.05 mol / L, and the concentration of the trisodium citrate in the electroplating solution is 0.015 mol / L.
5. A method for producing ammonia by nitrate reduction, characterized in that: The electrocatalytic nitrate reduction to ammonia production catalyst according to claim 1 or 2 is used as a self-supporting integrated electrode to electrocatalytically reduce nitrate to produce ammonia in an electrochemical system.
Citation Information
Cited By
Cobalt hydroxide / copper heterogeneous interface catalyst with oxygen vacancy and application thereof
CN120866863A
